1999
DOI: 10.1046/j.1523-1747.1999.00532.x
|View full text |Cite
|
Sign up to set email alerts
|

Procyanidin Oligomers Selectively and Intensively Promote Proliferation of Mouse Hair Epithelial Cells In Vitro and Activate Hair Follicle Growth In Vivo11The authors disclosed conflict of interest.

Abstract: We have previously reported that proanthocyanidins extracted from grape seeds possess growth-promoting activity toward murine hair epithelial cells in vitro and stimulate anagen induction in hair cycle progression in vivo. This report constitutes a comparison of the growth-promoting activity of procyanidin oligomers and the target cells of procyanidins in the skin. Results show that procyanidin dimer and trimer exhibit higher growth-promoting activity than the monomer. The maximum growth-promoting activity for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
2
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 41 publications
5
82
2
1
Order By: Relevance
“…Previous studies reported that procyanidins have a stronger protective effect than their monomeric units in vitro (Lotito et al 2000, Arteel et al 1999, Takahashi et al 1999, Zhu et al 2002. This is different from the present result in which epicatechin demonstrated stronger protection than Dimer B2.…”
Section: Resultscontrasting
confidence: 99%
“…Previous studies reported that procyanidins have a stronger protective effect than their monomeric units in vitro (Lotito et al 2000, Arteel et al 1999, Takahashi et al 1999, Zhu et al 2002. This is different from the present result in which epicatechin demonstrated stronger protection than Dimer B2.…”
Section: Resultscontrasting
confidence: 99%
“…Furthermore, in terms of the effect of GPC on normal cell proliferation, cells treated with different doses of GPC had higher proliferative activities than the normal control, and an obvious dose-dependent response was obtained: the higher dose of GPC the cells received, the better cell proliferative activity observed. This indicated that GPC promoted cell proliferation in normal hepatocytes and our data is similar to the previous reports on GPC stimulating hair cell growth [10,11] . The stimulating effect of GPC in normal cell proliferation might be associated with its inhibitory effect on endogenous free radicals-generated cell injury, and the precise mechanism needs further investigations.…”
Section: Cell Proliferation Is a Physiological Characteristicsupporting
confidence: 92%
“…1), respectively. [12][13][14]17,23) We therefore tried to compare the effects of GP and AP with the effects of PSE on IgE and IgG1 levels in mice-immunized with OVA. Orally administered AP at a dose of 30 mg/kg/d significantly reduced IgE levels, whereas AP and GP did not reduce total IgG1 levels at the same dose (Figs.…”
Section: Discussionmentioning
confidence: 99%